Entropy generation analysis in MHD mixed convection of hybrid nanofluid in an open cavity with a horizontal channel containing an adiabatic obstacle. (November 2017) - Hussain, S.; Ahmed, Sameh E.; Akbar, T.
Highlights: An increase in Ha causes the decreases of average Nu, SHT and ST . An increase in Ri increases the mixed convection modes as well as the rate of heat transfer. An increase in the Re and ϕ causes an enhancement in Nu and entropy generation tools. Heat transfer irreversibility is dominating than the fluid friction irreversibility for low Ha . Abstract: A computational analysis has been performed in a horizontal channel with an open cavity filled with hybrid nanofluid of Al 2 O 3 - Cu -water having an adiabatic square obstacle inside. The bottom wall of the cavity is taken as hot while all the rest walls of the channel and cavity are adiabatic except the left end of the channel which is taken as cold. Three different vertical locations of the obstacle are considered. The governing partial differentials equations are solved via Galerkin finite element method in space and the Crank-Nicolson in time. Newton method is utilized to cope with discretized nonlinear systems of equations and the Gaussian elimination method has been applied to solve the associated linear subproblems in each nonlinear iteration. The emerging parameters are Richardson number ( 0.01 ⩽ Ri ⩽ 20 ), nanoparticle volume fraction ( 0.0 ⩽ ϕ ⩽ 0.04 ), ( 1 ⩽ Re ⩽ 200 ) and Hartmann number ( 0 ⩽ Ha ⩽ 100 ) . Calculations of the streamlines, isotherms, average Nusselt number and entropy generation will be the main focus of interest in this study.